Modelling field robot software using AADL - Larsen, Morten (Technical Report Electronics and Computer Engineering, 2016)
This report contains a technical description and example on how robotic systems based on a distributed communication middleware can be modelled in AADL, incorporating hardware aspects. Furthermore analyses on the extra-functional properties such as bus-bandwidth and end-to-end latency are performed.